China-Venezuela Relations: China Dilemmatic Options towards Venezuela Crisis and the Role of China Community of Common Destiny Principles in Maintaining Cooperation - Alamsyah, Mirah Satria; Wiranata, Indra Jaya (JASSP, 2021)
Oil prices directly impact Venezuela's circumstance due to 95% of their revenue come from oil export. Since 2013, oil prices drop significantly compared to the previous year. Thus, the crisis hits Venezuela severely. The impacts not only feel in domestic level but also in international level. China is Venezuela's bilateral partner that was impacted by the Venezuela crisis. Venezuela failed to fulfill their oil export to China to pay their loan in the oil-for-loan diplomacy scheme. Thus, their cooperation failed to fulfill the economic gain. However, China still shows the action that favorable Venezuela. Backing up non-intervention toward Venezuela in the UN, provide new loan and adjust the payment of the previous loan also diversify their investment in Venezuela. This paper argues that this action is no more for merely material gain. But it is the action that is based on the newly ideational aspect of China's foreign policy, which is the China Community of Common Destiny. Thus, this research will analyze how this rhetoric idea involves China's action towards Venezuela. Also, this research will address their relations and China's diplomatic option toward their relations with Venezuela in crisis circumstances.